The evolution of human altruism towards non-kin through sexual selection - Phillips, Tim (2008)
Altruistic or selfless behaviour is a major puzzle for evolutionary biology which predicts competition between organisms in the struggle for existence. One explanation for altruism towards non-kin proposes that it evolved as a reliable signal of individual quality to others, including potential mates. It is thus possible to see altruistic traits as handicaps that act as indicators of the phenotypic and genetic quality under sexual selection. Here, I also suggest that sexual selection mechanisms other than the handicap principle might have favoured the evolution of altruism towards non-kin.